Corruption Prevention: Government Internal Control System and Organizational Culture as Moderation - Rusli, Riswandi; Yamin, Nina Yusnita; Kamase, Haryono Pasang; Betty, Betty (Penelitian dan Pengembangan Ilmu, 2025)
This study examines and analyzes the effect of government internal control systems and organizational culture interaction on corruption prevention. This research was conducted in village governments in Marawola, Dolo, and Sigi Biromaru sub-districts, Central Sulawesi, involving 150 village government officials as respondents. This research uses quantitative methods with primary data in the form of questionnaires. SmartPLS 4.0 was used as an analysis tool. The results found that a strong internal control system, as indicated by a healthy control environment and regular monitoring activities, is effective in preventing corruption. An organizational culture that emphasizes open communication and information is proven to strengthen corruption prevention efforts. However, the results of this study also show that an organizational culture that does not support the separation of duties and authorities will weaken corruption prevention efforts. These findings suggest that building a strong system is not enough, it is important to build a culture that supports transparency and accountability.